Enterotoxemia en equino atribuida a Clostridium Perfringens tipo A - Sáez B., Sylvia; Cifuentes M., Alejandro; Jara S., Otilia; Rex O., Astrid (Avances en Ciencias Veterinarias, 1992)
En un caballo de tiro se presentó una muerte repentina que a la necropsia evidenció un cuadro enterotoxémico, confirmado posteriormente por el aislamiento de Clostridium perfringens tipo A, de fuerte actividad de fosfolipasa C y de patrón electroforético (poliacrilamida-SDS) concordante con una cepa de referencia. Palabras claves: Enterotoxemia, equinos, Clostridium perfringens tipo A. Abstract A draft horse from a chilean well managed farm suddenly died, presenting at the necropsy an enterotoxemic syndrome which was confirmed by the isolation of Clostridium perfringens type A, with strong phospholipase C activity and corresponding SDS-PAGE electrophoretic pattern when compared with a reference strain. Key words: Enterotoxemia, horses, Clostridium perfringens type A.